Unpaid Work, Paid Work and Gender Inequality: An Analysis of Time Transfer Accounts for Turkey - ŞAHANOĞULLARI, NAZLI; Seçkin, Aylin; Georges, Patrick (Akademiai Kiado Zrt., 2024)
This paper provides a comprehensive assessment of the total (market and non-market) gender-based production and consumption activities of Turkish men and women at different stages of their life-cycle. Turkey, one of the few emerging economies within the OECD, offers an interesting case-study as its female labour force participation rate is one of the lowest among OECD countries. Our results show that time spent by Turkish women on household activities is, on average, 30 h a week, basically three times as much as men. In fact, the women-to-men time use ratio for unpaid work is roughly twice as much as the OECD average. We estimate that the monetary value of women unpaid household production exceeds 29% of GDP, while the corresponding estimate for men is around 8%. Using the concept of life-cycle deficit, we also show that Turkish men are dependent on housework undertaken by women over their entire lifetime, which is an almost unique feature in comparison to the European and OECD countries. Finally, unlike other OECD countries that have introduced disincentives to early retirement, Turkish men continue to retire early but retain their acquired habits of not sharing the burden of household work.
Keywords: Gendered Economy; Time Use; National Time Transfer Accounts; Emerging Economy; Household Production; Paid/unpaid Work; Women Labour Force Participation